Answer:
140°
Step-by-step explanation:
Supplementary angles sum to 180° , thus
angle = 180° - 40° = 140° ← other angle
The two equations given in the question are
y = - 3x
And
y = 6x - 9
Let us now substitute the value of y from the first equation to the second equation, we get
y = 6x - 9
- 3x = 6x - 9
-3x - 6x = - 9
- 9x = - 9
Multiplying both sides of the equation by -1 we get
9x = 9
x = 9/9
= 1
Now let us put the value of x in the first equation, we get
y = - 3x
= - (3 * 1)
= - 3
Answer:
-17/12
Step-by-step explanation:
-(2/3)-(3/4)
-(8/12)-(9/12)
-17/12
Answer: 12 answer is A
Step-by-step explanation: